Vaginoplasty with Amnion Graft: Management of Mayer-Rokitansky-Kuster-Hauser Syndrome - Bhandari, Srijana; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Tiwari, Kenusha Devi; Bharati, Sonu; Maharjan, Sunita (Journal of Nepal Health Research Council, 2024)
Mayer-Rokitansky-Kuster-Hauser syndrome also known as mullerian agenesis is a rare congenital condition in which there is absence of uterus along with upper vagina. Patient usually presents with primary amenorrhea with or without cyclical lower abdominal pain but have normal secondary sexual characters. Modified McIndoe Vaginoplasty with amnion graft is the commonest surgery performed worldwide. A 23 year old girl with normal secondary sexual characters presented with primary amenorrhea with cyclical lower abdominal pain; on examination blind vagina was present. Vaginoplasty with amnion graft was done and vaginal mould was placed. Vaginal dilatation with Hegar’s dilator was done weekly until 6 weeks. She is under regular follow-up at present and advised for regular manual dilation at home. McIndoe Vaginoplasty with amnion graft is a simple yet rewarding procedure especially in low resource countries like ours, with good success rate and with minimal postoperative complications. Keywords: Amnion graft; Mayer-Rokitansky-Kuster-Hauser Syndrome; Modified McIndoe Vaginoplasty; Primary amenorrhea; Secondary sexual characters.